Hemocyte-Mediated Phagocytosis in Crustaceans - Liu, Shan; Zheng, Shu-Cheng; Li, Yan-Lian; Li, Jun; Liu, Hai-Peng (Frontiers in Immunology, 2020)
Phagocytosis is an ancient, highly conserved process in all multicellular organisms, through which the host can protect itself against invading microorganisms and environmental particles, as well as remove self-apoptotic cells/cell debris in order to maintain tissue homeostasis. In crustacean, phagocytosis by hemocyte has also been well recognized as a crucial defense mechanism for the host against infectious agents such as bacteria and viruses. In this review, we summarized the current knowledge of hemocyte-mediated phagocytosis, in particular focusing on the related receptors for recognition and internalization of pathogens as well as the down-stream signal pathways and intracellular regulators involved in the process of hemocyte phagocytosis. We attempted to gain a deeper understanding of the phagocytic mechanism of different hemocytes and their contribution to the host defense immunity in crustaceans.